PENGARUH KOMPETENSI GURU, PERHATIAN ORANG TUA, DAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR QUR’AN HADIS - muhammad gaffarur rozi (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to determine the effect of teacher competence, attention of parents, and peers on the motivation to learn Qur'anic Hadiths of class X Madrasah Aliyah in East Lombok Regency. The research method used is a quantitative approach with descriptive correlational type. The study population was all students of class X Madrasah Aliyah in East Lombok with a cluster random sampling technique. The results showed: first, there was a positive and significant influence of teacher competence on student learning motivation, with a correlation number rx_1y = 0.405 and a coefficient of determination of R ^ 2 X_1Y = 0.164. second, there is a positive and significant influence of parental attention on student motivation, with a correlation number of rx_2y = 0.387 and a coefficient of determination of R ^ 2 X_2Y = 0.150. third, there is a positive and significant influence of peers on student learning motivation, with the correlation number rx_3y = 0.326 and the coefficient of determination of R ^ 2 X_3Y = 0.106; fourth, there is a positive and significant influence on teacher competence, the attention of parents and peers together on the learning motivation of class X students in the subject of the Qur'an Hadith Madarasah Aliyah in East Lombok Regency, with a correlation rate of rxy (1,2, 3) = 0.513 and the coefficient of determination is R ^ 2 xy (1,2,3) = 0.263.